THE RELEVANCE OF COMPUTERIZED ACCOUNTING INFORMATION AND ITS EFFECT ON IMPROVING THE EFFECTIVENESS OF EXTERNAL AUDITING IN YEMEN COMMERCIAL BANKS: A SURVEY STUDY - Alammari, Amro A. S.; Parameshwara (International Journal of Research -GRANTHAALAYAH, 2023)
The main objective of this study was to investigate the relationship between the relevance of computerized accounting information and the effectiveness of external auditing in Yemen commercial banks. To achieve this goal, the study used a quantitative research approach, and 350 questionnaires were distributed to workers at the administrative levels in Yemen commercial banks and external auditing offices that audit banks. The number of rounded questionnaires valid for statistical analysis reached 300, i.e., 86% of the distributed questionnaires. The findings of the regression model show that the unstandardized coefficient B for the relevance of CAIS is 0.724, which is significant as the p-value is less than 0.05.and this signifies that one-unit variation (increase) in the relevance of CAIS leads to a variation of 0.724 units of variation (raise) in the effectiveness of external audits in commercial banks in the Republic of Yemen. It was concluded that the computerized accounting systems were designed with relevancy in mind, which reflected favorably on the effectiveness of the external audit. This indicates that the results produced by computerized accounting information systems are effectively relevant to the results produced by an external audit. Overall, the study suggests that in order to improve the effectiveness of external auditing in Yemen commercial banks, it is important to ensure that the computerized accounting information being used is relevant and accurate. Therefore, it is safe to say that there is a positive connection between the relevance of computerized accounting information and the external audit's effectiveness.